Allocation of in-house services: Experimental comparison of allocation mechanisms - Thomas Elendner; R. Femerling (Universität Kiel, Institut für Betriebswirtschaftslehre; ZBW – Leibniz Information Centre for Economics, 2003)
In this paper we consider the problem of allocating scarce resources in a divisionalized company; the resources are made available by the headquarters and requested by profit centers (PCs). This problem was observed at a large german insurance company (LAGIC). Currently, the resources are allocated for free; for the future, LAGIC proposes to use an iterative allocation mechanism to solve the allocation problem. Alternatively, we present a combinatorial auction-based allocation mechanism. Within experimental tests the performance of these two mechanisms is analyzed. To this end, instances are generated motivated by the problem size and structure occurring at LAGIC.
Keywords: 650; Resource allocation; in-house services; combinatorial auctions; efficient allocation; winner determination; multidimensional binary knapsack problem; instance generator; Unternehmensdienstleistung; Organisationsstruktur; Allokation; Auktionstheorie; Versicherung; Theorie